Update Advances on C-Reactive Protein in COVID-19 and Other Viral Infections - Luan, Ying-yi; Yin, Cheng-hong; Yao, Yong-ming (Frontiers in Immunology, 2021)
Severe coronavirus disease 2019 (COVID-19) can manifest as a viral-induced hyperinflammation with multiorgan dysfunction. It has been documented that severe COVID-19 is associated with higher levels of inflammatory mediators than a mild disease, and tracking these markers may allow early identification or even prediction of disease progression. It is well known that C-reactive protein (CRP) is the acute-phase protein and the active regulator of host innate immunity, which is highly predictive of the need for mechanical ventilation and may guide escalation of treatment of COVID-19-related uncontrolled inflammation. There are numerous causes of an elevated CRP, including acute and chronic responses, and these can be infectious or non-infectious in etiology. CRP are normally lacking in viral infections, while adaptive immunity appears to be essential for COVID-19 virus clearance, and the macrophage activation syndrome may explain the high serum CRP contents and contribute to the disease progression. Nevertheless, for the assessment of host inflammatory status and identification of viral infection in other pathologies, such as bacterial sepsis, the acute-phase proteins, including CRP and procalcitonin, can provide more important information for guiding clinical diagnosis and antibiotic therapy. This review is aimed to highlight the current and most recent studies with regard to the clinical significance of CRP in severe COVID-19 and other viral associated illnesses, including update advances on the implication of CRP and its form specifically on the pathogenesis of these diseases. The progressive understanding in these areas may be translated into promising measures to prevent severe outcomes and mitigate appropriate treatment modalities in critical COVID-19 and other viral infections.